2014
DOI: 10.1038/mp.2014.60
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor β is essential for the differentiation of radial glial cells to oligodendrocytes in the dorsal cortex

Abstract: Several psychiatric disorders are associated with aberrant white matter development, suggesting oligodendrocyte and myelin dysfunction in these diseases. There are indications that radial glial cells (RGCs) are involved in initiating myelination, and may contribute to the production of oligodendrocyte progenitor cells (OPCs) in the dorsal cortex. Liver X receptors (LXRs) are involved in maintaining normal myelin in the central nervous system (CNS), however, their function in oligodendrogenesis and myelination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…In line with the prominent regulatory roles of LXRs in CNS myelination that we demonstrate in the cerebellum, Xu et al showed that LXRβ, by acting on OPC specification in another brain region, the dorsal cortex, is critical for white matter development and CNS myelination, especially in the corpus callosum (19). We provide evidence that LXR isoforms differentially affect CNS myelination.…”
Section: Discussionsupporting
confidence: 58%
“…In line with the prominent regulatory roles of LXRs in CNS myelination that we demonstrate in the cerebellum, Xu et al showed that LXRβ, by acting on OPC specification in another brain region, the dorsal cortex, is critical for white matter development and CNS myelination, especially in the corpus callosum (19). We provide evidence that LXR isoforms differentially affect CNS myelination.…”
Section: Discussionsupporting
confidence: 58%
“…Western blot was performed as described by Xu et al 18. Total protein was extracted from the brain tissues surrounding the hematoma region and at the ipsilateral SN.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of dopamine in the impaired striatum and ipsilateral substantia nigra (SN) of the ICH mice was measured using high-performance liquid chromatographyelectrochemical detection, as described previously. 18 The chromatographic data were exported and analyzed using ESA software (ESA, Inc). The area under the curve of a standard concentration of dopamine was used to compare the dopamine concentrations in the samples.…”
Section: High-performance Liquid Chromatography-electrochemical Detecmentioning
confidence: 99%
“…LXR knockout mice have reduced myelination in the cerebellum and sciatic nerve, coincident with motor deficits, and LXR activation by the synthetic ligand TO901317 increased expression of myelin-related genes [42,43]. Indeed, loss of LXRβ particularly was found to result in impaired locomotion and decreased myelination in the corpus callosum and optic nerve, and this coincided with a reduction in the differentiation of radial glial cells (RGCs) into oligodendrocyte progenitor cells (OPCs) during development [44]. It has also been observed in vitro that primary oligodendrocytes increase LXRβ expression during differentiation [45], and that the LXR agonist TO901317 stimulates oligodendrocyte differentiation [43], induces LXR target gene expression and mediates cholesterol efflux from oligodendrocytes [45].…”
Section: Lxr Cholesterol Regulation Participates In Myelinationmentioning
confidence: 99%